Test the Effectiveness of Grape Seed Extract as an Antidiabetic Drug In Male White Rats Wistar Strain - Ardiantya Sudarsono, Cristhofer; Wibowo, Wibowo; Sugiyanto, Sugiyanto; Riani Hasana, Ani (Riviera Publishing, 2023)
The research aims to know the effectiveness of grape seeds in lowering blood sugar levels in white rats. The research began with grape seed extraction using the maceration method. The results of macerate were given to white rats that were given grape seed extract samples at doses of 75 mg/200 grams BW, 125 mg/200 grams BW, and 250 mg/200 grams BW. The positive control was metformin, and the negative control was given distilled water. All were given treatment for 14 days. On days seven and 14, a blood sugar test was carried out to assess the effectiveness of grape seed extract. The results showed that of the five treatment groups, sample group I (extract at a dose of 75 mg/200 gram BW) and sample group III (extract at a dose of 250 mg/200 gram BW) affected reducing blood sugar levels in rats. This is proven by comparing blood sugar levels after being given alloxan on the seventh day in the two groups, showing better results in reducing blood sugar levels than the other groups. It can be concluded that grape seed extract can properly reduce blood sugar levels in white rats with type II diabetes mellitus.